2022
DOI: 10.3390/wevj13050073
|View full text |Cite
|
Sign up to set email alerts
|

Development and Simulation of Real-Time Early Warning Protection System for Electric Vehicle Charging Based on a Two-Layer Protection Model

Abstract: With the increase of fire problems of new energy vehicles (EVs), more and more attention has been paid to charging safety. Firstly, the charging safety problems and protection strategies in the power grid are summarized from the grid side, the charging equipment side, the vehicle side, and the operation platform side, and a solution for the vehicle side charging safety protection is proposed. Secondly, with regards to building a charging early warning protection system architecture, a real-time protection stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It is essential that the rectification and uniform voltage control of electric vehicles adhere to SAEJ1772 [154]. SAEJ2293 [155] defines the specifications for charging an EV from a utility or microgrid employing an off-board charger. In order to integrate the system, one must adhere to SAEJ2836 [155].…”
Section: Standards Of the Charging Stationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential that the rectification and uniform voltage control of electric vehicles adhere to SAEJ1772 [154]. SAEJ2293 [155] defines the specifications for charging an EV from a utility or microgrid employing an off-board charger. In order to integrate the system, one must adhere to SAEJ2836 [155].…”
Section: Standards Of the Charging Stationmentioning
confidence: 99%
“…SAEJ2293 [155] defines the specifications for charging an EV from a utility or microgrid employing an off-board charger. In order to integrate the system, one must adhere to SAEJ2836 [155]. e various standards, their scopes, types of charging, and year of implementation are summarized in Table 6.…”
Section: Standards Of the Charging Stationmentioning
confidence: 99%
“…With the development of the industry, the safety of EVs has become one of the hot issues, which is not only the key to ensuring the safety of life and property, but also an important guarantee for the rapid development of the EV market. Realizing the safety early warning of the power battery of EVs and establishing a perfect mechanism have become the focus [4,5]. It has been found that the thermal runaway of the battery is an important cause of the spontaneous combustion of the EV charging [6,7].…”
Section: Introductionmentioning
confidence: 99%